Penerapan Media Poster Sebagai Upaya Pencegahan Minuman Keras di Kalangan Remaja - Anggraini, Fina; Eni Fariyatul Fahyuni (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Poster media is the application of poster media to obtain accurate information related to students' achievements in mastering poster media. The purpose of this study focuses on the analysis of the application of poster media as an effort to prevent liquor among adolescents. This study is a category of descriptive qualitative research, and the data sources in the study include interviews, observations and documentation. Data analysis used in this research is data reduction, data presentation, and conclusion drawing. The results of the analysis of the application of poster media as an effort to prevent liquor among teenagers make attractive poster media and with the placement of images and the right writing so that students can easily read the poster media made by the researcher is quite easy and can be followed by teachers to help the learning process. Furthermore, the challenges and obstacles of poster media as an effort to prevent liquor among teenagers are: In addition, making posters manually is a job that has its own challenges. This includes the issue of cost and quality of the products produced. To improve learning and overcome current challenges more efficiently. Meanwhile, other obstacles include difficulty conveying the message clearly, the budget to print quality posters and no place to specifically attach poster media in schools.